The Use of LOTO (Lock-Out Tag-Out) For Preventing Occupational Accidents Among Heavy Equipment Mechanics - Aprizal Satria Hanafi; Qomariyatus Sholihah (Andalas University, Faculty of Public Health, 2017)
Unlocked energy in the machine can cause heavy equipment to move suddenly, it can hit the mechanics that are working. LOTO devices are required in this case. LOTO is a locking and labeling system for energy sources so that occupational accidents can be prevented. This study aim to know the difference of occupational accident cases on heavy equipment mechanics before and after using LOTO devices. A quasy experiment approach was used to evaluate occupational accidents. This design uses two group, intervention group, and control group, 32 heavy equipment mechanics were given LOTO device and 32 heavy equipment mechanics were not given LOTO device.Based on pre-evaluation, evaluation 1, and evaluation 2  there is a decrease in the number of occupational accidents in the intervention group after given LOTO device. Statistical test showed there was a difference in occupational accidents before and after the use of LOTO device on heavy equipment mechanics based on type of accidents (beaten, p = 0.001), (falling, p = 0.005), (pinched, p = 0.001), (pressed, p = 0.001), (crushed, p = 0.000).LOTO devices proved to be effective in preventing and reducing the number of occupational accidents in the heavy equipment mechanics.